An Analysis of the Development of the Chinese Fast Food Industry - Zhuang, Kexin; Jiang, Yanqing (Journal of Asian Business Strategy, 2016)
The Chinese food culture is worldwide well-known, yet the Chinese catering industry has not gained its due attention in its past two decades’ development. Western fast food has launched a forceful marketing campaign to the Chinese fast food industry. This paper therefore aims to analyze the existing problems of the Chinese fast food industry from the two main aspects of culture difference and market factors. Combining analysis of the current status and the prospective future trends, this paper provides some strategies from the brand effect, cultural characteristics, chain management and personnel training, which expects to update the concept for the Chinese fast food industry and then promote the scientific development of Chinese fast food industry.